2022
DOI: 10.1297/cpe.2022-0005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sensor-augmented pump therapy for neonatal diabetes mellitus: a case series

Abstract: . Neonatal diabetes mellitus (NDM) is a rare metabolic disorder that is mainly present in the first 6 months of life and necessitates insulin treatment. Sensor-augmented pump (SAP) therapy has been widely used in children with type 1 diabetes mellitus, but its use in patients with NDM is limited. We report three patients with NDM who received SAP therapy using the MiniMed™ 640G system starting in the neonatal period. Two patients were treated for 3 months, and one patient continued treatment up to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…SAP therapy is effective in patients with type 1 diabetes, regardless of age ( 34 ). Some studies have reported the benefits of CSII and CGM in patients with NDM ( 10 , 15 , 17 , 19 , 35 ). Three previous studies have shown that CGM is useful not only for insulin therapy, but also for switching to oral SU in patients with NDM with the KCNJ11 variant ( 19 , 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAP therapy is effective in patients with type 1 diabetes, regardless of age ( 34 ). Some studies have reported the benefits of CSII and CGM in patients with NDM ( 10 , 15 , 17 , 19 , 35 ). Three previous studies have shown that CGM is useful not only for insulin therapy, but also for switching to oral SU in patients with NDM with the KCNJ11 variant ( 19 , 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, patients with KCNJ11 and ABCC8 mutants are treated with oral sulfonylurea (SU) rather than insulin injection ( 3 ). Some studies have reported the effectiveness of continuous subcutaneous insulin infusion (CSII) and continuous glucose monitoring (CGM) in patients with NDM receiving insulin therapy ( 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ). However, few studies have reported the effectiveness of CGM in patients with NDM during and after switching to oral SU ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found SAP therapy to be effective for our patient with TNDM for the following reasons: First, a PLGM system predicted hypoglycemia from CGM data and automatically suspended insulin delivery by CSII [ 5 ]. Few prior reports have described the effectiveness of a PLGM system in patients with TNDM [ 6 ]. Here, we demonstrated how a PLGM system could function correctly in an infant patient without causing hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%